2013
DOI: 10.1021/jp311271p
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Modified Stable Colloidal Gold Nanostars for the Photothermolysis of Cancer Cells

Abstract: The preparation and properties of plasmonic gold nanostars (Au NSs) modified with a biopolymer chitosan are reported. The colloidal stability of Au NSs at the physiological pH of 7.5 and their performance in the photothermolysis of cancer cells in vitro were compared with those of gold nanorods (Au NRs). The optical characteristics of chitosan-modified Au NSs dispersed in a medium with pH = 7.5 had higher stability than those of chitosan-capped NRs because of the slower aggregation of NSs. At pH = 7.5, the chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 62 publications
3
36
0
2
Order By: Relevance
“…Dual mode MR/CT imaging functionality can be easily realized by assembly of dendrimerentrapped AuNPs onto preformed Fe 3 O 4 NPs [37] or by hydrothermal synthesis of Fe 3 O 4 /Au composite NPs [56,57]. In another work, Liu and coworkers have shown that Au NSs having a strong surface plasmon resonance (SPR) band at NIR region can be prepared from Au seeds in the growth solution using silver ion complexes as growth inhibitors [58]. Likewise, Au NSs with magnetic Fe 3 O 4 or Fe cores formed by exposing the core/shell Fe 3 O 4 @Au NPs (seeds) or Fe seeds into the Au growth solution can be used for gyromagnetic imaging of cells or fluorescence imaging/photothermal destruction of cancer cells [59,60], while Fe 3 O 4 @Au nanostars (NSs) formed by the reduction of Au(III) onto the dextran-coated Fe 3 O 4 NPs with hydroxylamine as a seeding agent displayed five distinct functions (aptamer-based targeting, MR imaging, optical imaging, photothermal therapy and chemotherapy) [34].…”
Section: Introductionmentioning
confidence: 99%
“…Dual mode MR/CT imaging functionality can be easily realized by assembly of dendrimerentrapped AuNPs onto preformed Fe 3 O 4 NPs [37] or by hydrothermal synthesis of Fe 3 O 4 /Au composite NPs [56,57]. In another work, Liu and coworkers have shown that Au NSs having a strong surface plasmon resonance (SPR) band at NIR region can be prepared from Au seeds in the growth solution using silver ion complexes as growth inhibitors [58]. Likewise, Au NSs with magnetic Fe 3 O 4 or Fe cores formed by exposing the core/shell Fe 3 O 4 @Au NPs (seeds) or Fe seeds into the Au growth solution can be used for gyromagnetic imaging of cells or fluorescence imaging/photothermal destruction of cancer cells [59,60], while Fe 3 O 4 @Au nanostars (NSs) formed by the reduction of Au(III) onto the dextran-coated Fe 3 O 4 NPs with hydroxylamine as a seeding agent displayed five distinct functions (aptamer-based targeting, MR imaging, optical imaging, photothermal therapy and chemotherapy) [34].…”
Section: Introductionmentioning
confidence: 99%
“…By comparing populations at the single-probe level, it was found that the count rate variance from a SERS NP is at least as good as that observed for fl uorescent emission of Alexa Fluor 633. The preparation of gold nanostars modifi ed with FITC-labeled chitosan was also reported later [ 87 ]. These modifi ed GNS had a higher colloidal stability at physiological pH and they are more suitable mediators in cell photothermolysis due to the slower aggregation.…”
Section: Functionalization Of Gns With Dyesmentioning
confidence: 87%
“…The most attractive advantage of electrostatically assisted APTESfunctionalized surface assembly method is that a substrate with a very homogeneous SERS signal and large area can be fabricated without sophisticated equipment. Plasmonic gold nanostars were also modifi ed with a biopolymer chitosan [ 87 ]. The chitosan-modifi ed nanostars dispersed in a medium with pH = 7.5 had higher stability than those of chitosan-capped nanorods because of the slower aggregation of GNS.…”
Section: Other Examples Of Functionalization Of Gnsmentioning
confidence: 99%
“…GNS modifi ed with a biopolymer chitosan with such improved properties were reported [ 43 ]. An in vitro photothermolysis experiment on J5 cancer cells showed that energy fl uences of 23 mJ/cm 2 are necessary to cause complete death of J5 cells incubated with 4 μg/mL chitosancapped GNS.…”
Section: Application Of Gns For Thermal Therapymentioning
confidence: 99%